Construção e caracterização de um alternador axial horizontal para aerogeradores de energia elétrica com base em imãs de NdFeB. - Nascimento, Pedro dos Santos (Universidade Federal do Tocantins, 2023)
Clean energy sources are major investments in the last few decades, while the environmental ones are a source of energy for new sources of energy to diversify and universalize a world energy source. But despite all the investment being made in this area, researchers estimate that about 16% of the world’s population still do not have access to electricity. Although Brazil has a mostly clean energy matrix, we are still distancing ourselves from energy and leaving unconventional energy generation, such as solar, wind and biomass. The predominant source of electric power in Brazil is hydroelectric, which uses the kinetic and potential energy of the waterfalls to convert to electric energy. The wind generation capacity available in Brazil can reach 143 GW of power, but currently they are exploited in about 9% of this wind potential. Wind turbines are used to convert energy and wind into electricity, can be structured according to an application and a geography where wind farms are built, to obtain the best use of the energy potential of the site. The present work aims to construct a construction, design and characterization of a horizontal flow of axial flow, that will be applicable in aerogenerators. Through the industry the fact that it is possible to use the knowledge acquired throughout the course, the materials loaded, the low cost of easy handling. The construction of this prototype was based on the technique of building and handling DIY objects. Do it yourself, that is, do it yourself, that technique simplifies an object construction and its own application.